2013
DOI: 10.1007/978-1-62703-791-4_6
|View full text |Cite|
|
Sign up to set email alerts
|

Biophysical and Proteomic Characterization Strategies for Cysteine Modifications in Ras GTPases

Abstract: Cysteine is one of the most reactive amino acids and is modified by a number of oxidants. The reactivity of cysteines is dependent on the thiol pKa; however, measuring cysteine pKa values is nontrivial. Ras family GTPases have been shown to contain a free cysteine that is sensitive to oxidation, and free radical-mediated oxidation of this cysteine has been shown to be activating. Here, we present a new technique that allows for measuring cysteine pKa values using a fluorescent detection system with the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…As Rac1 Cys 18 can be selectively modified by oxidized glutathione at physiological pH, we investigated whether the p K a of the Rac1 Cys 18 thiol is altered relative to a typical free cysteine thiol by measuring the cysteine reactivity of Rac1 WT and Rac1 C18S to ABD-f. We used the thiol-modifying reagent ABD-f, which preferentially reacts with the thiolate form of cysteine [59], to measure thiol reactivity over a wide pH range, as described previously by us for Ras [60]. ABD-f fluorescence was measured from pH 5.5 to 8.5 for Rac1 WT and Rac1 C18S (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As Rac1 Cys 18 can be selectively modified by oxidized glutathione at physiological pH, we investigated whether the p K a of the Rac1 Cys 18 thiol is altered relative to a typical free cysteine thiol by measuring the cysteine reactivity of Rac1 WT and Rac1 C18S to ABD-f. We used the thiol-modifying reagent ABD-f, which preferentially reacts with the thiolate form of cysteine [59], to measure thiol reactivity over a wide pH range, as described previously by us for Ras [60]. ABD-f fluorescence was measured from pH 5.5 to 8.5 for Rac1 WT and Rac1 C18S (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NAC can activate the Ras-ERK (extracellular signal-regulated kinase) pathway in vitro through non-antioxidant mechanisms, protecting neuronal cells from death in the absence of trophic factors. Since Ras proteins contain essential reactive cysteines, it was suggested that NAC could trigger Ras by its reducing capability [ 385 , 386 ]. Some analyses showed that NAC could defend human neurons from the cerebral cortex against death induced by Aβ-amyloid 1−42 [ 187 ], causing p35/Cdk5 activation and decreasing phosphorylation/deactivation of the MLK3-MKK7-JNK3 signaling pathway [reviewed in 1].…”
Section: Modulation Of Cysteinet By N -Acetyl-cyst...mentioning
confidence: 99%
“…Previous studies from our group and others have shown that several cysteine residues in a subset of RAS superfamily GTPases have a lower pKa relative to that of a free cysteine (12)(13)(14)(15).…”
Section: Kras G12c Exhibits a Perturbed Cysteine Pka By Chemical Modi...mentioning
confidence: 76%
“…KRAS and other RAS superfamily GTPases have previously been shown to be sensitive to cysteine oxidation both in vitro and in cellular contexts (12)(13)(14)(15). With the observed sensitivity of KRAS G12C to chemical ligation by acrylamides like AMG 510 and ARS-853 and our NMR data demonstrating the lowered pKa of the G12C cysteine, we hypothesized that this cysteine could also be sensitive to modification by intracellular oxidizing agents.…”
Section: Kras G12c Is Sensitive To Oxidative Modification In Vitro An...mentioning
confidence: 94%